Etika Penggunaan Smarthphone Dalam Berkomunikasi Mahasiswa Prodi MIK Stikes Santa Elisabeth Medan - Pomarida Simbolon; Nagoklan Simbolon; Irma Novitasari Br. Sihotang; Selviani Damayanti Br. Sipayung; Angelia Pasaribu; Nayanda Privanezha Hao (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Ethics is a branch of axiology, namely the science of values, which focuses on the search for right and wrong or in another sense, moral and immoral. Smartphones are one of the results of technological developments that have advanced capabilities where students are one group of smartphone users. This research aims to increase students' knowledge about the ethics of using smartphones in communication. This research uses a survey method, namely by giving a survey questionnaire regarding understanding of ethics in communication and its prevention to students. The results of counseling and education for 19 students of the Health Information Management Study Program showed that the average knowledge of the community at the pretest was 92.6% and at the posttest it was 98.9%, which shows an increase in the average knowledge of students.